Team-Based Questioning Battles in Construction and Building Engineering Educational Environments: A Useful Tool for Engaging Active Learning in the Classroom - Pablo Pujadas; Stanislav Aidarov (MDPI AG, 2024)
This manuscript presents a comprehensive exploration of an innovative active learning approach implemented in a Master's Degree in Construction Engineering program. The pedagogical intervention involved a series of competitive battles among student teams, wherein each team formulated and presented multiple-choice questions to their peers. The study aims to provide a detailed account of the implementation process, assess the effectiveness of this approach, and evaluate its impact on students' learning and motivation. The assessment was conducted through triangulation of experiences, surveys, and interviews. The results provide key insights into how Team-Based Questioning Battles can foster highly competitive environments, enhancing the learning experience, understanding, and retention of concepts, all while motivating and engaging students.